Genetic analysis of Sumatran elephants in seblat natural ecotourism park based on partial of mitochondrial cytochrome B gene - Sipriyadi,; Yansen,; Bujana, Ardea; Eni Suryanti,; Cahyadi, Muhammad; Kusminanto, Richi Yuliavian; Muslim, Choirul; Naibaho, Teti; Monica Anggraini, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Sumatran elephant (Elephas maximus sumatranus Temminck, 1847) is one of the Asian elephant sub-species distributed in Sumatera Island and classified as endangered species due to hunting and high habitat fragmentation. This study aimed to analyze the genetic relationship of Sumatran elephants based on the mitochondrial cytochrome b gene (Cyt b). Blood samples were collected from 11 elephants in Seblat Natural Ecotourism Park. Based on mt-DNA Cytochrome b gene analysis, low genetic diversity was found in the Sumatran elephant population, indicated by 99-100% sequence similarity among elephant samples. Phylogenetic analysis showed that all elephants were in the same clade and has a close relationship with Borneo elephants. Additionally, the Median-joining network illustrated only two haplotypes in the Sumatran elephant population. The low genetic diversity of the Sumatran elephant indicates that a strategic breeding program should be seriously taken into account to prevent the Sumatran elephant from extinction.